2015
DOI: 10.1002/jrs.4661
|View full text |Cite
|
Sign up to set email alerts
|

High temperature Raman study of UO2: A possible tool forin situestimation of irradiation-induced heating

Abstract: Recently, in situ Raman setups under irradiation become available, and uranium dioxide is one of the most studied compounds. This paper reports the temperature dependence of the only Raman‐active mode in fluorine UO2. Besides the interest in terms of phonon anharmonicity knowledge, this can be used to estimate the heating induced by irradiation: The frequency shift and width of the T2g peak can be used as an internal indirect probe of the local temperature in the 20–590 °C range. Copyright © 2015 John Wiley & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The Raman setup was developed for the in situ measurements under irradiation or at high temperature (see details in). The setup (50‐mW CW 532nm laser, Renishaw RA100 spectrometer of 250‐mm focal length and equipped with a 1800‐l/mm grating) presents great performances and can be occasionally brought to the field: it can be qualified as portable according to Colomban .…”
Section: Volcano Sites and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman setup was developed for the in situ measurements under irradiation or at high temperature (see details in). The setup (50‐mW CW 532nm laser, Renishaw RA100 spectrometer of 250‐mm focal length and equipped with a 1800‐l/mm grating) presents great performances and can be occasionally brought to the field: it can be qualified as portable according to Colomban .…”
Section: Volcano Sites and Experimental Methodsmentioning
confidence: 99%
“…In this frame, in October 2013, we brought the extreme conditions spectrometer of the CEMHTI lab to the Piton de la Fournaise volcano for field and rear‐base characterization of natural volcanic samples. This paper relates the preliminary results of the field campaign.…”
Section: Introductionmentioning
confidence: 99%
“…Guimbretiere and co‐workers reported a high temperature Raman study of UO 2 as a possible tool for in situ estimation of irradiation‐induced heating. They found that the frequency shift and width of the T2g peak can be used as an internal indirect probe of the local temperature in the 20‐590 °C range . Jiang et al .…”
Section: High Pressure and Temperature Studiesmentioning
confidence: 99%
“…Raman spectroscopy has been recently reported as a suitable technique for the identification of lava and minerals in a recent volcanic environment and can be implemented remotely . Moreover, accurate temperature measurement is a key point for the understanding of lava flow dynamics and the Raman spectral data allow an estimation of the targeted sample temperature through references measurements or Stokes/anti‐Stokes (S/AS) intensity ratio …”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy has been recently reported as a suitable technique for the identification of lava and minerals in a recent volcanic environment [4,5] and can be implemented remotely. [6,7] Moreover, accurate temperature measurement is a key point for the understanding of lava flow dynamics [8,9] and the Raman spectral data allow an estimation of the targeted sample temperature through references measurements [10,11] or Stokes/ anti-Stokes (S/AS) intensity ratio. [12][13][14][15][16] In this study, we report on the development and implementation of remote field Raman system dedicated to study the medium temperature minerals in active volcanic environments.…”
Section: Introductionmentioning
confidence: 99%